Implementation of Protection Services for Women and Children Victims of Violence at Daerah Istimewa Yogyakarta: An Institutional - Muhammad Khozin; Nur Faidati; Gerry Katon Mahendra (Indonesian Association for Public Administration (IAPA), 2020)
Cases of violence against women and children in Daerah Istimewa Yogyakarta (DIY) in 2019 has reached 1,469 cases. This condition requires a special attention from the Government. The implementation of protection services for women and children victims of violence in DIY is carried out by P2TPAKK